APLIKASI SINBIOTIK UNTUK PENCEGAHAN INFEKSI INFECTIOUS MYONECROSIS VIRUS PADA UDANG VANAME (Litopenaeus vannamei) (Synbiotic Application for Prevention of Infectious Myonecrosis Virus Infection in White Shrimp (Litopenaeus vannamei)) - Widanarni Widanarni; Sukenda Sukenda; Ghita Ryan Septiani (Universitas Syiah Kuala, 2016)
This study aimed to evaluate the effectiveness of dietary synbiotic at different giving frequencies on growth, immune responses, and resistance of white shrimp infected by infectious myonecrosis virus (IMNV). Synbiotic used in this study was combination of probiotic Vibrio alginolyticus SKT-b and prebiotic oligosaccharides extracted from sweet potatoe (Ipomoea batatas L). Doses of probiotic and prebiotic used were 1% and 2% (w/w), respectively. The white shrimps (0.493±0.035 g) were divided into five treatments consisting of A and B (without supplementation of synbiotic: (A) positive control; (B) negative control), C (daily synbiotic supplementation), D (twice a week synbiotic supplementation), and E (weekly synbiotic supplementation). After 30 days of feeding trial, white shrimps were infected by IMNV (except negative control). The results showed that daily growth rate of white shrimp on all synbiotic treatments (C, D, and E) ranged from 6.93±0.025-6.97±0.019% and had higher values than controls (A and B) (P0.05). Meanwhile, feed conversion value in C and D (1.54±0.142 and 1.58±0.117) were lower than controls (P0.05). Supplementation of synbiotic with different frequencies also affected survival rate of white shrimp after the challenge test with IMNV; daily synbiotic supplementation (C) resulted in a 50% higher survival rate than positive control (P0.05). This was associated with immune responses parameters values of synbiotic treatment (before and after the challenge test) which were better than positive control. In conclusion the addition of synbiotic in feed resulted in higher growth performances, immune responses,and resistance of white shrimp to IMNV infection.